Optical characterization and bandgap engineering of flat and wrinkle-textured FA0.83 Cs0.17 Pb(I1 − xBrx)3 perovskite thin films - Tejada Esteves, Alvaro (2018)
The complex refractive indices of formamidinium cesium lead mixed-halide (FA0.83Cs0.17Pb(I1 − xBrx)3) perovskite thin films of compositions ranging from x = 0 to 0.4, with both flat and wrinkle-textured surface topographies, are reported. Films are characterized using a combination of variable angle spectroscopic ellipsometry and spectral transmittance in the wavelength range of 190 nm to 850 nm. Optical constants, film thicknesses and roughness layers are obtained point-by-point by minimizing a global error function, without using optical dispersion models, and including topographical information supplied by a laser confocal microscope. To evaluate the bandgap engineering potential of the material, the optical bandgaps and Urbach energies are then accurately determined by applying a band fluctuations model for direct semiconductors, which considers both the Urbach tail and the fundamental band-to-band absorption region in a single equation. With this information, the composition yielding the optimum bandgap of 1.75 eV for a Si-perovskite tandem solar cell is determined.